THE OLDEST EDIACARAN BIOTA OF THE URALS - Bekker Y.R. (My University, 1992)
The Bakeyevo biota, the oldest biota discovered in the folded area of the Urals, is described for the first time, and the important stratigraphic consequences of this discovery are examined. The discovery of the Bakeyevo biota extends the stratigraphic range of the Ediacaran fauna in the late Precambrian deposits of the folded area of the Urals. The Bakeyevo biota differs from the Ediacaran fauna and trace fossils in the younger deposits of the Vendian in the Urals, possibly indicating a variation in the Edicaran complex over time. The discovery of the Bakeyevo biota makes it possible to trace and substantiate the boundary horizons of the Vendian and Riphean stratons.
Keywords: Ediacaran; Precambrian::Proterozoic::Neoproterozoic::Ediacaran; Докембрий::Протерозой::Неопротерозойская::Эдиакарий